3D-printed Total Mandibular Prosthesis: A Rare Case Report - Ryuichi Hoshi; Paula Marcella Silva Drago; Henrique Mascarenhas Villela; Gabriela Gayer Sheibler; Daniel Serra Cassano; Fernanda Barros Silva de Pedreira Barbosa; Lissa Hoshi; Isadora dos Santos Lima (Medical Research and Its Applications Vol. 6, 2024)
The study aimed to introduce a new customized total mandibular prosthesis with 3D printing fabrication. The need for whole mandibular bone reconstruction and replacement is fortunately rare, but it is an extremely challenging topic in maxillofacial surgery, due to its functional implications. CAD-CAM techniques development has opened new broad horizons in the surgical planning of complex maxillofacial reconstructions, in terms of accuracy, predictability, and functional cosmetic results. The review of the literature has revealed a small number of scientific reports on total mandibulectomy including the condyles, with only eleven cases from 1980. Richieri-Costa-Pereira syndrome (RCPS) is a rare genetic disease with an autosomal recessive inheritance pattern characterized by craniofacial alterations such as microsomia, Pierre-Robin sequence and mandibular cleft. Only three cases of total mandibular rehabilitation with a customized prosthesis have been published, and none have described a patient born with a mandibular cleft. With the aid of computer-aided design/computer-aided manufacturing technology, virtual surgical planning, and customized manufacturing of surgical materials, the rehabilitation of this case became attainable. Despite achieving intriguing results, making definitive treatment recommendations for this type of case remains challenging. Additional clinical data should be added to this topic in future studies.